Diagnosis statement in the case of "decapitated hypertension": opinion on the issue - S. A. Boytsov; S. S. Yakushin; N. N. Nikulina (Российский кардиологический журнал)
The article discusses the statement of the diagnosis of hypertension (HTN) with severe left ventricular systolic dysfunction and the resulting decrease in systolic blood pressure (BP) to target levels or hypotension ("decapitated hypertension").The current Russian guidelines on HTN in adults and heart failure (HF) do not consider this situation. The used classifications of HTN by its degree in untreated patients and the achievement of the target BP level by antihypertensive therapy cannot correctly reflect the situation in this case, since HTN as such no longer exists, but the diagnosis as a chronic disease continues to exist.The authors propose to expand the existing classification by introducing the term "history of HTN", which correctly reflects the discussed period of disease, allows HTN to be included in the diagnosis, substantiates the unacceptability of using antihypertensive therapy in this period, as well as the difficulties in prescribing maximum doses of HF medications.